2012
DOI: 10.3390/medicina48030024
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Complex Cardiac Rehabilitation on Manifestation of Risk Factors in Patients with Coronary Heart Disease

Abstract: Background. Each year more than 4.3 million people in Europe will die of cardiovascular disease. Therefore, the implementation of simple interventions such as smoking cessation, weight loss, improved diets, and increased exercise is the top priority in prevention and rehabilitation programs. The aim of this study was to evaluate the impact of complex rehabilitation on the manifestation of risk factors and cardiac events in patients with coronary heart disease. Material and Methods. A total of 140 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
1
11
0
1
Order By: Relevance
“…However, it is worth noting that our study participants had relatively lower LDL levels even at baseline, compared to that in the study by Kubilius et al, where the baseline LDL levels in the intervention and control groups were 3.7 ± 0.8 mmol/L and 3.0 ± 1.4 mmol/L respectively. Given that reductions in LDL, TC and FBG were also observed in previously conducted studies 6 , 7 , 11 , our study results provide support that community-based CR programmes are able to improve lipid profiles and FBG in cardiovascular patients.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, it is worth noting that our study participants had relatively lower LDL levels even at baseline, compared to that in the study by Kubilius et al, where the baseline LDL levels in the intervention and control groups were 3.7 ± 0.8 mmol/L and 3.0 ± 1.4 mmol/L respectively. Given that reductions in LDL, TC and FBG were also observed in previously conducted studies 6 , 7 , 11 , our study results provide support that community-based CR programmes are able to improve lipid profiles and FBG in cardiovascular patients.…”
Section: Discussionsupporting
confidence: 88%
“…Power and Sample Size Calculations programme version 3.1.2 was used to calculate the sample size for a study of a continuous response variable between independent intervention and control groups of patients in a 1:2 ratio. Sample size estimation was based on the hypothesis of this study that improvements in LDL levels will be at least that of a previous study by Kubilius et al , where the LDL mean difference between cardiovascular patients in the intervention and control groups was 1.1mmol/L 7 . Assuming the response within patients in the intervention group was normally distributed with standard deviation (SD) of 2.5 mmol/L, a minimum of 61 and 122 cardiovascular patients in the intervention and control groups respectively was required in order to reject the null hypothesis that the population mean between the two comparison groups are equal, with 80% power and type I error (α) less than 0.05.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We located a Canadian study with 126 participants in traditional CR [20] and a European trial with 68 patients with medical management but no CR or lifestyle program. [21] The data in both studies permitted calculation of risk factor changes from baseline to 3 months on subjects providing virtually all requested data, comparable to the FULL analyses in this study. In the study of traditional CR, three risk factors (SBP, DBP, and HDL) all showed significant improvements that exceeded those of the Ornish and MBMI programs.…”
Section: Discussionmentioning
confidence: 63%
“…In the no lifestyle study, three risk factors (SBP, SBP, and BMI) showed significant improvements (declines) since baseline, one risk factor (HDL) showed a significant deterioration (increase) over baseline, while two risk factors (total cholesterol and LDL) showed no significant change. [21] Surprisingly, the pure controls achieved greater 3-month improvements in SBP and DBP than the lifestyle programs. This is probably because the pure controls had elevated average baseline blood pressures (SBP 150/DBP 92), whereas those of Ornish (129/72) and MBMI (135/73) participants were normal.…”
Section: Discussionmentioning
confidence: 97%